Consistency and aggregation in individual choice under uncertainty - Jeff Birchby; Gary Gigliotti; Barry Sopher (Rutgers University, Department of Economics, 2011)
It is common in studies of individual choice behavior to report averages of the behavior under consideration. In the social sciences the mean is, indeed, often the quantity of interest, but at times focusing on the mean can be misleading. For example, it is well known in labor economics that failure to account for individual differences may lead to incorrect inference about the nature of hazard functions for unemployment duration. If all workers have constant hazard functions independent of duration, simple aggregation will nonetheless lead to the inference that the hazard function is state-dependent, with the hazard of leaving unemployment declining with duration of unemployment. Similarly, a recent study in psychology has shown that the learning curve a monotonically increasing function of response to a stimuli, is better understood as an average representation of individual response functions that are, in fact, more step-function-like. As such, the learning curve as commonly understood is a misleading representation of the behavior of any one individual.
Keywords: C9; D8; 330; uncertainty; prospect theory; aggregation; consistency; uncertainty; prospect theory; aggregation; consistency